1, 3‐Diaryl‐β‐diketone Organic Crystals with Red Amplified Spontaneous Emission. Issue 12 (28th September 2016) - Tang, Baolei; Zhang, Houyu; Cheng, Xiao; Ye, Kaiqi; Zhang, Hongyu
Abstract: In this study, 1‐[4‐(dimethylamino)phenyl]‐3‐(1‐hydroxynaphthalen‐2‐yl)propane‐1, 3‐dione (DPHND) was designed and synthesized to construct red‐emissive organic solids. Although DPHND was weakly yellow fluorescent in organic solvents, its emission intensity showed a significant enhancement when a relatively large amount of poor solvent was added, and displayed typical aggregation‐induced enhanced emission (AIEE). Notably, the crystals formed by a solution‐diffusion approach showed bright red fluorescence ( λ em =621 nm), which was greatly redshifted by about 60 nm compared with that in solution. Molecules in crystals took a planar conformation and formed a herringbone packing structure, which effectively avoided π⋅⋅⋅π interactions, and hence contributed to the enhancement of the fluorescent quantum yield. The fluorescence spectrum of the long striplike crystals of DPHND gradually narrowed accompanied by a dramatic enhancement of the intensity when the pump energy of the laser beam was increased (355 nm), which indicated that these red‐emissive crystals displayed typical amplified spontaneous emission (ASE). In addition, DPHND with an extended π‐conjugated structure clearly improved its thermostability compared with the previously reported analogues, which may pave the way for its application in future electrically driven organic solid‐state lasers. Abstract : In the red : Highly efficient red‐emissive organic crystals have been constructed based on a solution‐state faint emissive 1, 3‐diaryl‐β‐diketone skeleton and the synthesized crystals display amplified spontaneous emission (ASE; see figure).